Putative interaction of brush cells with bicarbonate secreting cells in the proximal corpus mucosa - Eberle, Julia A.; Müller-Roth, Kai L.; Widmayer, Patricia; Chubanov, Vladimir; Gudermann, Thomas; Breer, Heinz (Frontiers in Physiology, 2013)
The gastric epithelium is protected from the highly acidic luminal content by alkaline mucus which is secreted from specialized epithelial cells. In the stomach of mice strong secretion of alkaline fluid was observed at the “gastric groove”, the border between corpus and fundus mucosa. Since this region is characterized by numerous brush cells it was proposed that these cells might secrete alkaline solution as suggested for brush cells in the bile duct. In fact, it was found that in this region multiple cells express elements which are relevant for the secretion of bicarbonate, including carbonic anhydrase (CAII), the cystic fibrosis transmembrane conductance regulator (CFTR) and the Na+/H+ exchanger (NHE1). However, this cell population was distinct from brush cells which express the TRP-channel TRPM5 and are considered as putative sensory cells. The location of both cell populations in close proximity implies the possibility for a paracrine interaction. This view was substantiated by the finding that brush cells express prostaglandin synthase-1 (COX-1) and the neighbouring cells a specific receptor type for prostaglandins. The notion that brush cells may be able to sense a local acidification was supported by the observation that they express the channel PKD1L3 which contributes to the acid responsiveness of gustatory sensory cells. The results support the concept that brush cells may sense the luminal content and influence via prostaglandins the secretion of alkaline solution.